Cognitive remediation for negative symptoms of schizophrenia: A network meta-analysis. (March 2017) - Cella, Matteo; Preti, Antonio; Edwards, Clementine; Dow, Tabitha; Wykes, Til
Abstract: Cognitive remediation (CR) is a treatment targeting cognitive difficulties in people with schizophrenia. Recent research suggested that CR may also have a positive effect on negative symptoms. This meta-analysis investigates the effect of CR on negative symptoms. A systematic search was used to identify all randomized-controlled trials of CR in people with schizophrenia reporting negative symptoms outcomes. Levels of negative symptoms at baseline, post-therapy and follow-up, sample demographics and treatment length were extracted. Study methodological quality and heterogeneity were addressed. Negative symptoms standardized mean change was calculated using Hedges's g and used as the main outcome. The search identified 45 studies reporting results for 2511 participants; 15 studies reported follow-up outcomes. CR was associated with a reduction of negative symptoms (most conservative model g  = − 0.30; 95% CI: − 0.36, − 0.22) at post-therapy compared with treatment as usual and this effect was larger at follow-up ( g  = − 0.36; 95% CI: − 0.51, − 0.21). Drop-out rate was comparable between conditions. Network meta-analysis confirmed CR was superior to TAU and TAU plus active control or adjunctive treatment. No evidence of publication bias was found. Studies with more rigorous methodology were associated with larger negative symptom reduction ( g  = − 0.40; 95% CI: − 0.51 to − 0.30). Although negative symptoms have not been considered a primary target for CR, this intervention can have small to moderate beneficial effects on this symptom cluster. Future research should explore in detail the active mechanisms responsible for negative symptom reduction and the relationship between cognitive and negative symptoms in schizophrenia. Highlights: This is the first study on the effect of Cognitive Remediation (CR) on negative symptoms in people with schizophrenia. The results demonstrate a small to moderate effect of CR on negative symptoms (effect size g =  − 0.30). Negative symptom reduction is maintained at follow-up (effect size 95% g =  − 0.36). Studies with more robust methodology show a larger negative symptom reduction (effect size g =  − 0.40). There were no differences in drop-out rates between individuals randomized to CR and the control conditions suggesting that this intervention is acceptable.